To solve the equation, we need to simplify the expression on the left side.
Starting with -2(6x - 5), we can distribute the -2 to each term inside the parentheses:
-2 * 6x + (-2) * (-5)
This simplifies to:
-12x + 10
Now, we have the equation:
-12x + 10 = 4
To isolate the variable x, we need to get rid of the constant term 10. We can do this by subtracting 10 from both sides:
-12x + 10 - 10 = 4 - 10
Simplifying further:
-12x = -6
Finally, to solve for x, we need to isolate it by dividing both sides of the equation by -12:
(-12x) / -12 = (-6) / -12
This simplifies to:
x = 1/2
Therefore, the solution to the equation is x = 1/2.
Solve the equation shown. -2(6x - 5) = 4
1 answer